MAKNA CINTA DALAM LIRIK LAGU BISMILLAH CINTA KARYA SIGIT PURNOMO: ANALISIS SEMIOTIKA FERDINAND DE SAUSSURE - Abu Barzah, Ahmad Zahrowii Danyal; Al Anshory, Abdul Muntaqim (Hasta Wiyata, 2022)
Music is a communication activity by using sound to convey a message to be expressed with a song. The song has a meaning as a literary work which is almost the same as poetry but is conveyed by playing melodies and harmonies. The song starts from a lyric in the form of stanzas created by an author aimed at conveying the message expressed. The messages contained in the lyrics of the created songs can be themed on friendship, motivation, love, and others. This study aims to determine and interpret the meaning of love contained in the lyrics of a song entitled Bismillah Cinta by Sigit Purnomo. This study uses the semiotic approach of Ferdinand De Saussure which makes the analogy of language as a signified and a signifier. This type of research uses descriptive and qualitative analysis. The source of data used in this research is the lyrics of a song entitled Bismillah Cinta by Sigit Purnomo. Through the analysis of the lyrics of the song, the results of this study reveal and convey the meaning that love is a feeling of trust that is trying to be expressed. The belief that everything is easy to pass and does not make the heart sway. Love teaches the meaning of that something we do must be accompanied by confidence without any anxiety and if there is no way out then asking Allah is the best way to solve it